A Complete Clinical Guide to Indigestion (Dyspepsia) (Homoeopathy for All, 2025)
Indigestion refers to sensation of  pain, discomfort or burning in the  upper abdominal region. The clinical  term for indigestion is dyspepsia,  derived from the Greek word  “dyspeptos” where “dys” means  “bad” or “difficult” and “peptos”  means “to digest”. Indigestion is not  a disease itself but rather a group  of digestive symptoms, including  belching, bloating, heartburn,  nausea, and vomiting. Indigestion  can be occasional or chronic in  nature. Occasional indigestion is  often linked to lifestyle factors while  chronic indigestion is indicative of a  more serious underlying condition  requiring medical evaluation.
Keywords: influence gut function; gastrointestinal conditions; gastroesophageal reflux disease (GERD); digestive discomfort